Beyond Leidenfrost levitation: A thin-film boiling engine for controlled power generation. (1st April 2021) - Agrawal, Prashant; Wells, Gary G.; Ledesma-Aguilar, Rodrigo; McHale, Glen; Sefiane, Khellil
Highlights: We present a thin-film boiling engine with a manual control of the power output. We support the weight of the rotors and indirectly vary the pressure in the vapor layer. We control the power output by changing the gap between the rotor and substrate. We achieve about 3.5 times increase in efficiency compared to levitation-based engines. An analytical model is used to characterize and explain the rotation. Abstract: Overcoming friction between moving components is important for reducing energy losses and component wear. Hydrodynamic lubrication via thin-film boiling provides an opportunity for reduced friction energy and mass transport. A common example of such lubrication is the Leidenfrost effect, where a liquid droplet levitates on a cushion of its own vapor on a surface heated to temperatures above the liquid's boiling point. An asymmetry in this vapor flow, self-propels the droplet on the surface due to viscous drag, converting thermal energy to mechanical motion, like a heat engine. Although levitation significantly reduces friction, the induced self-propulsion depends on substrate geometry and material properties, which limits dynamic propulsion control. Therefore, the ability to control the power output is a significant challenge in realizing operational mm and sub-mm scale virtually frictionless engines. Here, we present a thin-film boiling engine where we control the power output mechanically. The rotor, which comprises of a working liquid coupled to a non-volatile solid, is manually positioned over a heated turbine-inspired stator in a thin-film boiling state. We show that by controlling the position of the rotor over the substrate the power output from the rotation can be controlled above and below the Leidenfrost temperature ( 250 °C). We explain these experimental observations using a hydrodynamic analytical model. Additionally, we achieve propulsion outputs almost 4 times higher than levitation-based propulsion systems. The ability to control the rotation characteristics of such virtually frictionless engines allows potential applications in extreme environments such as at microscales or for space and planetary exploration.